An interesting case of progressive dyspnoea and diffuse mediastinal adenopathy in a 25-year-old man. Issue 1 (March 2021) - Cullivan, Sarah; Morris, Joseph; McCormack, Ciara; Alameeri, Amel; Gaine, Sean P.; McCullagh, Brian
A 25-year old man was admitted to hospital with a 12-month history of progressive dyspnoea and fatigue, with an acute deterioration over the preceding 2 weeks. He denied any significant past medical history, was a lifelong non-smoker and had moved to Ireland from Brazil with his family 1 year prior. On presentation, he was hypoxic, with peripheral oxygen saturations of 79% on room air and tachycardic at 110 beats·min −1 . Examination revealed a loud pulmonary component of the second heart sound, but was otherwise unremarkable, as he was clinically euvolaemic, with clear lung fields and there were no audible cardiac murmurs. Chest radiograph demonstrated prominent hilar vasculature (figure 1). Mediastinal adenopathy, septal line thickening, centrilobular ground glass opacities on CT and a markedly reduced T LCO in a young patient with pulmonary hypertension, should alert the clinician to this potential diagnosis https://bit.ly/3cfe9pX